2015
DOI: 10.1007/s00261-015-0361-8
|View full text |Cite
|
Sign up to set email alerts
|

MR enterography in Crohn’s disease: current consensus on optimal imaging technique and future advances from the SAR Crohn’s disease-focused panel

Abstract: MR enterography is a powerful tool for the non-invasive evaluation of patients with Crohn's disease (CD) without ionizing radiation. The following paper describes the current consensus on optimal imaging technique, interpretation, and future advances from the Society of Abdominal Radiology CD-focused panel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 47 publications
1
49
0
2
Order By: Relevance
“…100,101 CT enterography may result in suboptimal bowel distension without adequate patient compliance with oral contrast consumption. MRI optimized to evaluate the small bowel has also shown good sensitivity for the detection of Crohn’s disease 102 and small bowel tumors. 103 One recent series of 150 patients comparing the results of CT and MRI enterography for detecting small bowel tumors found that the sensitivity of MRI (93%) was actually higher than CT (76%; p=0.04).…”
Section: Resultsmentioning
confidence: 99%
“…100,101 CT enterography may result in suboptimal bowel distension without adequate patient compliance with oral contrast consumption. MRI optimized to evaluate the small bowel has also shown good sensitivity for the detection of Crohn’s disease 102 and small bowel tumors. 103 One recent series of 150 patients comparing the results of CT and MRI enterography for detecting small bowel tumors found that the sensitivity of MRI (93%) was actually higher than CT (76%; p=0.04).…”
Section: Resultsmentioning
confidence: 99%
“…Recent data suggest that cross-sectional imaging may be useful in determining response to therapy, assessing bowel healing, and monitoring disease progression (6). The Society of Abdominal Radiology (SAR) formed a Crohn's Disease-Focused Panel, which has established standards for the technical performance of these examinations (Appendix 1) (7)(8)(9). CTE and MRE are now performed across a range of institutions, with the radiologic literature focusing on the technical aspects of diagnosis and identification of mural inflammation or penetrating complications, such as fistula and abscess, using various acquisition methods and imaging findings.…”
mentioning
confidence: 99%
“…MRE is highly accurate in detecting internal fistulas in CD, with sensitivities ranging from 71-100% and specificities from 92-100% (13,14). MRE is superior to CTE in detecting internal and perianal fistulas (15,16), has the major advantage of lacking ionizing radiation (11,(15)(16)(17) and has better contrast resolution (10,18). Therefore, MRE is the imaging modality of choice in CD, especially in young patients and for those requiring repetitive imaging (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…MRE is superior to CTE in detecting internal and perianal fistulas (15,16), has the major advantage of lacking ionizing radiation (11,(15)(16)(17) and has better contrast resolution (10,18). Therefore, MRE is the imaging modality of choice in CD, especially in young patients and for those requiring repetitive imaging (17,18). Findings of CD on MRE are thickened bowel wall (>3 mm), increased wall enhancement, bowel wall edema, ulceration, perimural inflammation, and lymph node enhancement.…”
Section: Discussionmentioning
confidence: 99%